A fiber optic approach for cement placement and hydration assessment of deep geothermal boreholes - Johannes Hart; Berker Polat; Christopher Wollin; Martin Lipus; Felix Schölderle; Toni Ledig; Philippe Jousset; Thomas Reinsch; Charlotte M. Krawczyk (Scientific Reports)
Abstract Achieving well integrity is mandatory for a geothermal well’s safe and sustainable operation. One of the most critical steps is the success of the primary cementing. Conventional monitoring only shows discrete snapshots after completion of the cement job. However, optical fiber sensors enable monitoring of the entire cementing process. Here, we investigate the cement placement and early hydration for a surface casing at a geothermal site in Munich, Germany. We show that distributed dynamic strain rate sensing (DDSS or DAS) allows for tracking rising fluid interfaces, determining the setting time of cement, and assessing the cement job’s success at each depth. We used DDSS and DTS (distributed temperature sensing) with a fiber optic cable permanently deployed behind the casing and combined the results with operational data, a model for the rise of fluids in the borehole, and laboratory experiments to estimate the cement setting phase. Our approach enables monitoring all phases of primary cementing, which can increase the success rate of achieving well integrity. Furthermore, it can reduce costs and improve society’s acceptance of deep geothermal wells in urban areas.